2016
DOI: 10.1007/s12325-016-0438-y
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Effect of Intravenous Acetaminophen for Postoperative Pain Management on Length of Stay and Inpatient Hospital Costs

Abstract: IntroductionThe provision of safe, effective, cost-efficient perioperative inpatient acute pain management is an important concern among clinicians and administrators within healthcare institutions. Overreliance on opioid monotherapy in this setting continues to present health risks for patients and increase healthcare costs resulting from preventable adverse events. The goal of this study was to model length of stay (LOS), potential opioid-related complications, and costs for patients reducing opioid use and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 49 publications
(40 reference statements)
3
24
0
2
Order By: Relevance
“…These findings add to the real world evidence estimating the comparative effectiveness of IV versus oral APAP. Previous research of multimodal pain management including IV APAP versus opioid monotherapy also suggests that IV APAP for acute postoperative pain improves patient outcomes and reduces hospital resource use [ 35 39 ]. As health care practitioners move toward multimodal approaches to synergize distinct pain medications, increase analgesia, and reduce adverse events [ 2 ], this real world evidence is critical to help inform providers and hospital administrators about the clinical and economic benefits of IV APAP.…”
Section: Discussionmentioning
confidence: 99%
“…These findings add to the real world evidence estimating the comparative effectiveness of IV versus oral APAP. Previous research of multimodal pain management including IV APAP versus opioid monotherapy also suggests that IV APAP for acute postoperative pain improves patient outcomes and reduces hospital resource use [ 35 39 ]. As health care practitioners move toward multimodal approaches to synergize distinct pain medications, increase analgesia, and reduce adverse events [ 2 ], this real world evidence is critical to help inform providers and hospital administrators about the clinical and economic benefits of IV APAP.…”
Section: Discussionmentioning
confidence: 99%
“…These findings also align with biological evidence of the potential interaction between morphine and oral APAP due to the inhibition of gastrointestinal motility by opioids, leading oral APAP to provide inadequate pain control in the surgical setting 15 . From the perspective of treatment protocol and medical policy development, this real world evidence is critical to help inform providers and hospital administrators about the benefits of IV APAP as part of multimodal analgesia 5,6,[16][17][18] . The body of literature regarding the use of IV APAP for postoperative pain consistently finds associations supporting the use of IV APAP to improve patient outcomes and reduce hospitalization costs 5,[16][17][18] .…”
Section: Discussionmentioning
confidence: 99%
“…and LOS by 18.5% by the use of IV acetaminophen, with estimated cost savings of $4.5 million. 19 Another retrospective study evaluating the use of IV acetaminophen after spinal surgery reported decrease in postoperative opioid use, but they did not find decreased subsequent antiemetic or laxative use. 8 However, their study size was small (n = 34), and the acetaminophen doses were not standardized.…”
Section: Discussionmentioning
confidence: 97%
“…Our results are consistent with prior research findings in adults undergoing orthopedic surgeries, where use of IV acetaminophen was found to decrease costs and lower LOS . In adults undergoing obstetric, cardiovascular, colorectal, and orthopedic surgeries, authors report decreased opioid‐related complications by 28.7% and LOS by 18.5% by the use of IV acetaminophen, with estimated cost savings of $4.5 million . Another retrospective study evaluating the use of IV acetaminophen after spinal surgery reported decrease in postoperative opioid use, but they did not find decreased subsequent antiemetic or laxative use .…”
Section: Discussionmentioning
confidence: 99%